DEVELOPMENT AND EVALUATION OF CONTROLLED POROSITY OSMOTIC TABLETS OF CANDESARTAN CILEXETIL USING INCLUSION COMPLEX SYSTEM - ASHWIN KUMAR K,; GRACE RATHNAM, (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: This study aims to enhance the solubility of BCS Class-II drug candesartan cilexetil (CC) by forming inclusion complexation with hydroxypropyl β-cyclodextrin (CDs) and develop a controlled-release osmotic tablet for 24-h release. Methods: Solubility of Candesartan was enhanced using hydroxypropyl β-CDs at a molar ratio1:1 and analyzed for drug content and drug release profile. Fourier transform infrared interaction studies were conducted in drug complex and excipients. Core tablets were prepared with various ratios of osmogens (mannitol: Lactose monohydrate). Pre-compression studies were performed, and cellulose acetate solution containing sorbitol as pore-forming agent was used to coat the tablet cores, achieving 3% and 5% weight gain. The core tablets were subjected to post-compression tests assessing parameters such as thickness, weight variation, hardness, friability, and drug content, while the coated tablets underwent in vitro dissolution studies. Data obtained were subjected to drug release kinetics and formulation F6 was subjected to stability studies. Results: Characterization confirmed good flow properties, mechanical stability, and uniform drug content. Formulation F6 coated with cellulose acetate, showed 97.33% drug release at 24 h, following zero-order kinetics. Stability studies indicated that F6 remained stable for 3 months, with no notable changes in attributes such as appearance, drug content, and dissolution profile. Conclusion: This study successfully formulated a controlled drug delivery system for CC using controlled porosity osmotic delivery suggesting its potential for further development and clinical evaluation to enhance patient compliance and therapeutic efficacy.